Acupuncture modulates the frequency-specific functional connectivity density in primary dysmenorrhea - Liu, Li-Ying; Li, Xiang; Tian, Zi-Lei; Zhang, Qi; Shen, Zhi-Fu; Wei, Wei; Guo, Xiao-Li; Chen, Ling; Su, Meng-Hua; Yang, Lu; Yu, Si-Yi; Yang, Jie (Frontiers in Neuroscience, 2022)
Background The study aimed to investigate how acupuncture modulates brain activities across multiple frequency bands to achieve therapeutic effects in PDM. Methods A total of 47 PDM patients were randomly assigned to the verum acupuncture group and sham acupuncture group with three menstrual cycles of the acupuncture course. The fMRI scans, visual analog scale (VAS) scores, and other clinical evaluations were assessed at baseline and after three menstrual-cycles treatments. Global functional connectivity density (gFCD) analyses were performed between the pre-and post-acupuncture course of two groups at full-low frequency band, Slow-3 band, Slow-4 band, and Slow-5 band. Results After acupuncture treatments, the patients with PDM in the verum acupuncture group showed significantly decreased VAS scores (p<0.05). And frequency-dependent gFCD alternations were found in the verum acupuncture group, altered regions including DLPFC, somatosensory cortex, anterior cingulate cortex, middle cingulate cortex, precuneus, hippocampus, and insula. The sham acupuncture modulated regions including angular gyrus, inferior frontal gyrus, and hippocampus. The gFCD alternation in DLPFC at the Slow-5 band was negatively correlated with VAS scores in PDM patients following verum acupuncture. Conclusion These findings supported that verum acupuncture could effectively modulate frequency-dependent gFCD in PDM by influencing abnormal DLPFC at Slow-5 band and hippocampus at the Slow-3 band. The present outcome may shed light on enhancing the potency of acupuncture in clinical practice.